Revising the Metacognitive Awareness of Reading Strategies Inventory (MARSI) and testing for factorial invariance - Mokhtari, Kouider; Dimitrov, Dimiter M.; Reichard, Carla A. (Studies in Second Language Learning and Teaching, 2018)
In this study, we revised the Metacognitive Awareness of Reading Strategies Inventory (MARSI), a self-report instrument designed to assess students’ awareness of reading strategies when reading school-related materials. We collected evidence of structural, generalizability, and external aspects of validity for the revised inventory (MARSI-R). We first conducted a confirmatory factor analysis of the MARSI instrument, which resulted in the reduction of the number of strategy statements from 30 to 15. We then tested MARSI-R for factorial invariance across gender and ethnic groups and found that there is a uniformity in student interpretation of the reading strategy statements across these groups, thus allowing for their comparison on levels of metacognitive processing skills. We found evidence of the external validity aspect of MARSI-R data through correlations of such data with a measure of the students’ perceived reading ability. Given that this journal is oriented to second language learning and teaching, our article also includes comments on the Survey of Reading Strategies (SORS), which was based on the original MARSI and was designed to assess adolescents’ and adults’ metacognitive awareness and perceived use of ESL reading strategies. We provide a copy of the MARSI-R instrument and discuss the implications of the study’s findings in light of new and emerging insights relative to assessing students’ metacognitive awareness and perceived use of reading strategies.